REVEALING THE RELATIONSHIP BETWEEN HEARING HANDICAP AND TINNITUS SEVERITY: A CROSS-SECTIONAL STUDY ON CAUCASIAN ADULTS - Wan Mohamad, Wan Najibah; Hoare, Derek; Hall, Deborah (International Journal of Allied Health Sciences, 2019)
Introduction: While tinnitus is often associated with hearing loss, little is known regarding its relationship with hearing handicap. The aim of this study was to determine the correlation between Tinnitus Handicap Inventory (THI) and Hearing Handicap Inventory (HHI) questionnaires. Methods: Adults with tinnitus (n=200) aged 22 to 80 years participated in this study. Participants were classified accordingly to the category of tinnitus severity measured by the THI. Participants were instructed to fill in the aforementioned self-administered questionnaires. The 25-item THI consists of three subscales (emotional, functional and catastrophic) was used to assess tinnitus severity while HHI is composed of 25 items categorized under two subscales (emotional and situational) was used to assess hearing handicap. Results: A weak correlation was found between the total HHI and total THI scores (r = 0.31). When the emotional subscales were compared between the two questionnaires, a weak correlation was also noted (r=0.26). Conclusion: These findings clearly demonstrate that the THI measures a construct different to that of the HHI. That is, the hearing handicap questionnaire is not sufficient to predict tinnitus severity.